2014
DOI: 10.1111/jam.12658
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effect of combined fumaric acid and slightly acidic electrolysed water on the inactivation of food-borne pathogens and extending the shelf life of fresh beef

Abstract: Combined treatment of SAEW and FA can be a suitable hurdle technology reducing bacteria in fresh beef, substantially enhancing their microbial safety and decreasing pathogens growth during storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Among all the organic acids that are utilized as antimicrobial agents on meat (such as lactic acid and acetic acid), fumaric acid (FA) has been shown to exhibit strong bactericidal effects (Podolak and others , 1996). Treatment with the combination of SAEW and FA has been shown to prolong the shelf life of beef and pork with greater bactericidal effect as compared to individual treatments (Mansur and others ; Tango and others ). The meat industry has been using salts of organic acids such as calcium lactate, owing to their ability to increase flavor, prolong shelf life, and improve the microbiological safety of the products (Lawrence and others ; Naveena and others ; Selgas and others ).…”
Section: Hurdle Enhancement Of Ew With Other Treatmentsmentioning
confidence: 99%
“…Among all the organic acids that are utilized as antimicrobial agents on meat (such as lactic acid and acetic acid), fumaric acid (FA) has been shown to exhibit strong bactericidal effects (Podolak and others , 1996). Treatment with the combination of SAEW and FA has been shown to prolong the shelf life of beef and pork with greater bactericidal effect as compared to individual treatments (Mansur and others ; Tango and others ). The meat industry has been using salts of organic acids such as calcium lactate, owing to their ability to increase flavor, prolong shelf life, and improve the microbiological safety of the products (Lawrence and others ; Naveena and others ; Selgas and others ).…”
Section: Hurdle Enhancement Of Ew With Other Treatmentsmentioning
confidence: 99%
“…As a sanitizer, hypochlorous acid is 80 times more effective than an equivalent concentration of the hypochlorite ion (ClO − ) for inactivating Escherichia coli 17 . The application of SAEW at a near-neutral pH minimizes human health and safety issues from Cl 2 off-gassing while maximizing the utilization of the hypochlorous acid species 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Its bactericidal activity is attributed to a high concentration of hypochlorous acid (HOCl; approximately 95%) and high redox potential (Zhang et al ., ; Al‐Holy & Rasco, ). SAEW combined with ultrasonication, fumaric acid or medium temperatures show enhanced inactivation efficacy of microorganisms (Koide et al ., ; Forghani & Oh, ; Tango et al ., ). A previous study also showed that electrolysed water ice inhibited the growth of aerobic and psychrotrophic bacteria markedly in saury flesh during refrigerated storage (Kim et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, acidic electrolysed water was applied as a new pressure‐transmitting medium, and log reductions up to 6.08 and 5.71 log CFU g −1 were obtained in shrimp artificially contaminated with Vibrio parahaemolyticus and Listeria monocytogenes , respectively (Du et al ., ). SAEW combined with other interventions has been proven to be a stable and effective method to enhance the inactivation efficacy of bacterial spores (Forghani & Oh, ; Tango et al ., ; Mansur et al ., ).…”
Section: Introductionmentioning
confidence: 98%